2021
DOI: 10.1007/s00262-021-03061-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly differential count of circulating and tumor infiltrating immune cells in patients with non-HCV/non-HBV hepatocellular carcinoma

Abstract: Background Liver transplantation and liver resection are curative options for early hepatocellular carcinoma (HCC). The outcome is in part depended on the immunological response to the malignancy. In this study, we aimed to identify immunological profiles of non-HCV/non-HBV HCC patients. Methods Thirty-nine immune cell subsets were measured with multicolor flow cytometry. This immunophenotyping was performed in peripheral blood (PB) and tumor specimens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The opposite results obtained by Shi et al were interpreted by the authors as an effect of removing the tumor lesion, which might have had an immunosuppressive effect. Both effects might be present and differently pronounced dependent on tumor type, size, and differentiation, or for example, liver cirrhosis, which also can lead to immunosuppression [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposite results obtained by Shi et al were interpreted by the authors as an effect of removing the tumor lesion, which might have had an immunosuppressive effect. Both effects might be present and differently pronounced dependent on tumor type, size, and differentiation, or for example, liver cirrhosis, which also can lead to immunosuppression [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hepatitis or general chronic inflammation cannot be underestimated. Therefore, in our experimental work we have opted to investigate non-HBV/non-HCV patients to mitigate these biases [ 42 ]. Lastly, the invasiveness of the operation seems to be influencing the amount of immunosuppression deriving from the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibitory TME has an important influence on tumor immunity. Some scholars have found that in non-HBV/non-HCV HCC, although TILs secrete IFN-γ, they cannot kill cancer cells ( 143 ). Therefore, the conversion of inhibitory TME into immunoactive TME is a key focus for HCC treatment.…”
Section: The Value Of Tls For Phc Treatmentmentioning
confidence: 99%
“…The problems caused by chronic hepatitis B virus (HBV) infection continue to pose a major challenge to global health. 1 , 2 , 3 Although an effective preventive vaccine is available, it is of little use to people chronically infected with HBV. In addition, the existing treatment methods have limited efficacy and can not reliably eliminate all replication intermediates of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…The problems caused by chronic hepatitis B virus (HBV) infection continue to pose a major challenge to global health 1–3 . Although an effective preventive vaccine is available, it is of little use to people chronically infected with HBV.…”
Section: Introductionmentioning
confidence: 99%